The Phloem Intercalated With Xylem-Correlated 3 Receptor-Like Kinase Constitutively Interacts With Brassinosteroid Insensitive 1-Associated Receptor Kinase 1 and Is Involved in Vascular Development in Arabidopsis - Xu, Ke; Jourquin, Joris; Njo, Maria Fransiska; Nguyen, Long; Beeckman, Tom; Fernandez, Ana Ibis (Frontiers in Plant Science, 2022)
Leucine-rich repeat receptor-like kinases (LRR-RLKs) play fundamental roles in cell-to-cell and plant-environment communication. LRR-RLKs can function as receptors perceiving endogenous or external ligands, or as coreceptors, which stabilize the complex, and enhance transduction of the intracellular signal. The LRR-RLK BAK1 is a coreceptor for different developmental and immunity pathways. In this paper, we identified PXY-CORRELATED 3 (PXC3) as a BAK1-interacting LRR-RLK, which was previously reported to be transcribed in vascular tissues co-expressed with PHLOEM INTERCALATED WITN XYLEM (PXY), the receptor of the TDIF/CLE41 peptide. Characterization of pxc3 loss-of-function mutants revealed reduced hypocotyl stele width and vascular cells compared to wild type, indicating that PXC3 functions in vascular development in Arabidopsis. Furthermore, our data suggest that PXC3 might function as a positive regulator of the CLE41/TDIF-TDR/PXY signaling pathway.